Occurrence of pulsus alternans during anaesthesia of two dogs and one cat and its treatment. Issue 1 (19th October 2020) - Nicholls, D; Adami, C; Monticelli, P
Abstract : The authors report the occurrence of pulsus alternans, a condition characterised by the alternance of pulses of higher and lower amplitude, in two dogs and one cat under general anaesthesia. The presence of an underlying cardiac disease was confirmed in the cat but not in either dog, which – based on history and clinical findings – had presumably normal cardiovascular function before the anaesthetic. Possible mechanisms, including negative inotropy and haemodynamic and Frank‐Starling effects, as well as the role of general anaesthesia as the potential triggering factor, are discussed in this report. Ephedrine resulted in the successful treatment of pulsus alternans, as demonstrated by the return of normal pulse and synchronisation of heart and pulse rates in the cat and in one dog. In the other dog, pulse pattern and frequency returned to normal once the guidewire for central line placement was withdrawn.